The Taylor series of a function is a power series, all of whose derivatives match their corresponding derivatives of the function.

Let us derive the Taylor series of a function #f(x)#, centered at #c#.

Let

#f(x)=sum_{n=0}^infty a_n(x-c)^n#

#=a_0+a_1(x-c)+a_2(x-c)^2+cdots#,

where coefficients #a_1, a_2, a_3,...# are to be determined.

By taking the derivatives,

#f'(x)=a_1+2a_2(x-c)+3a_3(x-c)^2+cdots#

#f''(x)=2a_2+3cdot2 a_3(x-c)+4cdot3 a_4(x-c)^2+cdots#

#f'''(x)=3cdot2 a_3+4cdot3cdot2a_4(x-c)+5cdot4cdot3a_5(x-c)^2+cdots#

.

.

.

By plugging in #x=c#,

#f(c)=a_0=0! cdot a_0#

#f'(c)=a_1=1! cdot a_1#

#f''(c)=2a_2=2! cdot a_2#

#f'''(c)=3cdot2 a_3=3! cdot a_3#

.

.

.

#f^{(n)}(c)=n! cdot a_n#

By dividing by #n!#,

#a_n={f^{(n)}(c)}/{n!}#

Hence, we have the Taylor series of #f(x)#, centered at #c#

#f(x)=sum_{n=0}^infty{f^{(n)}(c)}/{n!}(x-c)^n#.

I hope that this was helpful.